The Relationsip Between Environmental Conditions and Communitiy Behavior the Incidence of Acute Respiratory Tract Infections (ARI) in Toddlers at the Lapandew - Eky Endriana Amiruddin; Nurkasmadeli; Taswin; Rininta Andriani; Wahyuddin; Muhamad Subhan; Darsal Zulfakar David (International Journal of Scientific Multidisciplinary Research, 2024)
This study aims to determine the relationship between environmental conditions and community behavior with ARI. The type of  research used is a cross sectional study. The population in the study were all toddlers and the sample was 220 respondents. Data collection techniques using questionnaires. Results showed There is a relationship between house ventilation and the incidence of ARI in toddlers p value = 0.014. residential density and the incidence of ARI in toddlers p value = 0.023. smoking habits and the incidence of ARI in toddlers p value =0.000. Habit of using wood fuel for cooking and the incidence of ARI in toddlers p value =0.000. Conclusion that all research variables, were related to the incidence of acute respiratory infections